Islamic Spiritual Counseling in Improving the Emotional Resilience of Broken Home Students at Muhammadiyah Middle School Tanjung Redeb - Khamam Khosiin; Darul Ihsan; Ahsan Hakim (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study aims to analyze the effectiveness of Islamic spiritual counseling in improving the emotional resilience of broken-home students at SMP Muhammadiyah Tanjung Redeb. The study used a descriptive qualitative approach with a phenomenological orientation. The main subjects were students from broken-home families, while supporting informants included Guidance and Counseling teachers, Islamic Education teachers, homeroom teachers, and the school principal. Data were collected through participatory observation, in-depth interviews, and documentation. The data were analyzed through data condensation, coding, thematic categorization, data display, and conclusion verification. The findings show that Islamic spiritual counseling provides an emotional safe space for students to express sadness, anger, anxiety, and disappointment without fear of judgment. The counseling process integrates a humanistic approach with Islamic values through empathy, acceptance, prayer, dhikr, muhasabah, sabr, ikhlas, tawakkul, and tazkiyatun nafs. These practices help students regulate emotions, reduce anxiety, control anger, accept family realities, and rebuild self-confidence. The study concludes that Islamic spiritual counseling is effective as a holistic school counseling model because it combines emotional support, spiritual strengthening, moral guidance, and character formation. This model is relevant for Islamic schools in supporting students who experience family problems and emotional vulnerability.